"Falling on One's Sword": A Response to the Principle Resignation Forum. Issue 3 (July 2018) - Mueller, Des
Several distinguished scholars have contributed previously to this debate and I have been privileged to consider their arguments. In doing so, I have been mindful that the realities of life frequently pierce the armor of high-minded principles. An important caveat on my views is that the debate is about senior officer resignation in the U.S. armed forces. A distant observer might therefore miss some of the important nuances at play, but it is difficult not to conclude that the U.S. armed forces exercise significant political influence in their own right and collectively through the Joint Chiefs of Staff. They are certainly major cogs in the formidably complex machinery of both government and politics.